Spatial and temporal dynamics of agricultural land carrying capacity (LCC): A case study of Jombang District, Indonesia - Siti Humaira An Nisaa; Fidel Albany Ku Jastin; Anta Pasha Tritama (BIO Web of Conferences)
Agriculture becomes one of the essential sectors in supporting food security. Nevertheless, in many cases around the world, vast urbanization often leads to an imbalance of resource consumption and its carrying capacity including the land. This paper explores the status of agricultural land carrying capacity from the perspective of spatial and temporal dynamics in Jombang District, Indonesia. Jombang is one of the regions in East Java Province that significantly contributes to crop production. More than 50% of the land use in Jombang is agricultural land. Yet, the spatial dynamics affected by several factors such as distance to the nearest city, industrialization, road infrastructure, and built-up density, as well as government policy on spatial planning might have some impacts on the agricultural land in Jombang during the last several years. To assess and extrapolate the existing and future agricultural land carrying capacity, we conducted three analyses comprising the following: (1) agricultural land cover change; (2) agricultural ecological footprint and its biocapacity; and eventually (3) the agricultural land carrying capacity. All the analyses are based on the temporal dynamics considering the past, the existing, and the future. The findings suggest that agricultural policy, spatial plan, and programs should be maintained continually towards surplus status of LCC.